A New Paradigm of Post New Normal School-Based Management - Yulista, Helda (PPSDP International Journal of Education, 2023)
In light of the new normal era, this study tries to define the new idea of school-based management. Methods of qualitative research were applied in this study. The methods used for data collecting included interviews, documentation, observation, and literature reviews. Analyses of descriptive and qualitative data were used. The administration of more community participation in school activities and school preparation from an IT perspective constitute the new paradigm of school-based management following the advent of the new normal period. Getting the word out about crucial school schedules, programs, learning activities, admissions for new students, and financial management of the school. The completion of IT infrastructure facilities and a rise in teacher IT proficiency are two components of school IT readiness. Efforts to raise the standard of Basic Education can be significantly impacted by community involvement and IT preparedness for the classroom.